Strong Women Never Mumble: Female Athlete Attitudes About Sexual Consent - McGovern, Jen (Journal of interpersonal violence, 2021)
Research demonstrating the effect of sports’ hypermasculine culture on athlete attitudes about sexual consent primarily focuses on men. Female athletes routinely engage with the same culture but their beliefs about sexual communication are rarely examined. This study examines the unique ways that athletic norms of hegemonic masculinity intersect with embodied lived experiences to influence female athletes’ perceptions of consent communication. Data were gathered from surveys and focus group interviews at a midsized university in the Northeast. The findings indicate that athletic women place emphasis on confidently saying “no” in ambiguous sexual situations. Data also show that female athletes’ attitudes about sexual consent differ from their nonathletic peers even though both groups experience many of the same sexual pressures. The research demonstrates how athletic women’s gendered practices are constituted by their status as women and as athletes and suggests that future training programs should aim to incorporate perspectives of women athletes.